Optimalisasi Intensitas Budaya Gotong Royong dalam Kegiatan Karang Taruna Ngudi Luhur Desa Kaliwungu, Kabupaten Semarang - Ruth Siwi Ningtyas,; Nani Mediatati, (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The tradition of gotong royong (mutual cooperation) is a deeply rooted cultural value in Indonesian society that reflects the spirit of solidarity, togetherness, and collective responsibility. As an integral part of local wisdom, it needs to be preserved and revitalized, especially among the younger generation. One of the key community-based youth organizations, Karang Taruna, holds a strategic role in empowering village communities and supporting national development. However, in practice, the intensity of gotong royong within the activities of Karang Taruna Ngudi Luhur in Kaliwungu Village remains relatively low. This study aims to explore the underlying factors contributing to the low participation in mutual cooperation activities and identify strategic efforts to enhance involvement. The research employed qualitative methods, including observation and interviews, to obtain comprehensive data. The data were analyzed using a descriptive qualitative approach. The findings revealed that low participation stems from both internal and external factors. Internal factors include an individualistic mindset, weak organizational management, and personal interests or job-related time constraints. External factors include cultural shifts, the erosion of traditional values, rapid technological development, socio-economic transformations, and insufficient support from local government authorities. To overcome these challenges, several strategic approaches were proposed: designing an annual activity program, evaluating existing activities, and delegating responsibilities based on individual competencies. Other strategies involve improving communication by leveraging digital platforms, implementing personal and persuasive approaches to members, and fostering collaboration with various stakeholders. These efforts aim to rebuild a culture of gotong royong that is adaptive to modern changes while still rooted in traditional values.